PENGARUH PENERAPAN PENDEKATAN LINGKUNGAN TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Ledina, Pelagia; Kresnadi, Hery; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to analyze the effectiveness of environmental approach implementation on towards IPA’s learning outcomes at grade V SDN 38 Pontianak Utara". This research employed an experimental method with a quasi-experimental research, exactly the Nonequivalent Control Group of experimental design. The sample was class V A and class V B SDN 38 Pontianak Utara that consisted of 24 students for class V A (experimental class) which was taught by using an environmental approach. While the class V B was the control group. The data instrument was the test of students’ learning outcomes in form of 50 multiple choice questions. The results of this research drawn that post-test experimental class was 79.4 and the post-test of control class was 69.32 then obtained t count of 3.7312 and t table α = 5%  (dk = 24        + 22 - 2 = 44) is 1.6762. It meant t count (3.7312)> t table (1.6762), then Ha is accepted. Thus, it can be concluded that there was an effectiveness of the implementation of environmental approach on towards  IPA’s learning outcomes at  grade V SDN 38 Pontianak utara.  The effect size (ES) calculation was obtained 0.71 (high criteria). It meant that the environmental approach implementation had big influence on student learning outcomes in learning IPA’S at grade V SDN 38 Pontianak Utara. Keywords:Environmental Approach, Learning Outcomes